A buckling mechanics approach to elastic modulus determination of glassy polymer films. Issue 1 (4th November 2018) - Rencheck, Mitchell L.; Rodriguez, Ricardo; Miller, Nolan A.; Davis, Chelsea S.
ABSTRACT: Column buckling mechanics were examined as a technique to determine the modulus of glassy polymer films that fail at very low strains in tension. As an alternative modulus measurement technique, free‐standing column buckling (FSCB) mechanics were investigated here. Given the film geometries and the critical buckling load, classical relationships can be used to determine the modulus. Several polymeric materials were tested and compared to uniaxial tensile values to determine the robustness and validity of the technique. Film geometries were varied from 4 to 18 mm in width and from 15 to 60 mm in length. The films were compressed in plane until buckling occurred and the critical buckling load was measured for each geometry. The critical buckling load increased as film width increased and decreased as film length increased, while the thickness was held constant for each material. For polyethylene terephthalate films, the elastic modulus was determined to be 3.06 ± 0.58 GPa. This FSCB‐determined modulus was compared to the elastic modulus obtained by tensile testing (3.54 ± 0.2 GPa). The modulus measurement technique presented here has the potential to be used experimentally to determine the elastic modulus of glassy polymer films that perform poorly in tension. © 2018 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys.2019, 57, 15–20 Abstract : Brittle polymeric films have difficulty being mechanically tested in tension. Column buckling mechanics relates a compressive load to the elastic modulus. Buckling experiments are able to be conducted with relative ease giving access to modulus characterization of brittle polymer films. By varying film geometries, the accuracy of a compressive elastic modulus characterization technique can be verified through modulus constancy.